Smart Campus: Concepts, Development and Future - Kaschel-Carcamo, H; Palominos-Belmar, P; Martin-Quijada, R; Arenas-Toledo, J (Institute of Electrical and Electronics Engineers Inc., 2022)
With the advent of the sanitary crisis there was a shift to the online courses that radically changed the education practices. Although most of the universities succeeded been resilient to ensure education continuity. Today, most universities are trying to implement solutions to make their campuses smart. The objective of this document is to show through a literature review, the future development direction of smart university campus and their associated concepts. The stages of development, the associated technologies and a proposal for a smart campus model from a Living-Lab approach are presented. © 2022 IEEE.
Keywords: Smart Campus; conceptual model; technology; university community